Feasibility and Acceptability of a Mobile Game to Support Smoking Cessation: Repeated Measures Study - Shelby Goodwin; Jessica A Nastasi; Schyler T Newman; Darion Rapoza; Bethany R Raiff (JMIR Publications, 2024)
BackgroundApproximately half of smokers attempt to quit, but 90% of these attempts fail. Video game-based interventions have the potential to address common barriers to evidence-based smoking cessation treatment, including high cost, lack of health care access, and low engagement. ObjectiveThe purpose of this study was to evaluate the feasibility and acceptability of a video game-based smoking cessation intervention called Inspired and its impact on the 7-day smoking point prevalence at the 30-day follow-up. MethodsUS adults (n=48) were recruited via the web to use Inspired on their smartphones for 7 weeks. The object of the game was to defend a healing tree against attackers. Levels of the game were unlocked twice daily when participants self-reported the number of cigarettes they smoked since the previous entry. Completion of the levels awarded players in-game currency, which could strengthen in-game abilities. Participants received additional in-game rewards to aid gameplay by submitting either smoking self-reports only or self-reports indicating abstinence, determined through random assignment. In addition, participants completed a web-based survey at intake, week 4, week 7, and the 30-day follow-up. ResultsOf the 48 participants, who had an average age of 39.8 (SD 10.7) years, 27 (56%) were female, 4 (8%) Hispanic, 37 (77%) White, and 27 (56%) employed; 26 (54%) earned <US $40,000 a year; and 14 (29%) lived in nonurban areas (eg, rural and suburban). There were no significant differences between the groups, so all outcome data were combined. Participants averaged 20.6 (SD 15.3) days of gameplay and reached a mean highest game level of 10.7 (SD 8.4), although there was a high degree of variability. Participants reported abstinence on 31.4% (SD 38.2%) of all cessation phase reports and averaged 5.4 (SD 9.8) consecutive abstinent smoke reports. For every 1 SD increase in the highest level achieved, there was a 27% increase in the percentage of abstinent samples and a 405% increase in longest continuous abstinence. At the 30-day follow-up, 23% (11/48) of the participants reported having not taken a cigarette puff in the prior 7 days and 31% (15/48) had spent at least 24 hours without smoking in the prior 14 days. On an 11-point scale, participants rated the intervention moderately favorably: if they had to do it again, they would use Inspired to help them quit (mean 6.4, SD 3.4), and Inspired was helpful in their current attempt to quit (mean 5.4, SD 3.6). ConclusionsThese results support the acceptability of Inspired. Although high dropout rates prevent conclusions on feasibility, a subset of the participants responded favorably. Scalable and accessible video game-based smoking cessation interventions could be the key to addressing the foremost cause of preventable morbidity and mortality in the United States. Trial RegistrationClinicalTrials.gov NCT03929003; https://clinicaltrials.gov/ct2/show/NCT03929003